Fabrication and Experimental Evaluation of a Small-Scale Pyrolysis Reactor for Coconut Shell Charcoal Production - Melvin Emil Simanjuntak; Jandri Fan H.T. Saragi; Muhammad Iqbal Murti; Prisca Caesa Moneteringtyas; Paini Sri Widyawati (DINAMIS, 2026)
The utilization of coconut shell biomass for small-scale charcoal production through pyrolysis offers a renewable energy alternative, yet the time-dependent evolution of charcoal properties during carbonization remains underexplored. This study aims to fabricate a small-scale fixed-bed pyrolysis reactor and experimentally evaluate the effect of pyrolysis time on coconut shell charcoal characteristics at a constant operating temperature of 400°C. The reactor was fabricated from carbon steel with an effective volume of 150.6 L. Pyrolysis experiments were conducted for 300 minutes, with charcoal samples collected at 30‑minute intervals. The results show that increasing pyrolysis time progressively reduced both charcoal yield and bulk density, with final values of 14.7 % and 6.67 kg/m³, respectively at 210 minutes, after which both stabilized. The carbonization process exhibited three distinct stages: early gradual devolatilization (30–120 min), rapid structural transformation (120–180 min), and stabilization (after 210 min). Visual observations revealed a transition from dark brown to deep black coloration with increasing residence time, followed by increased fragility at prolonged durations. The novelty of this work lies in the application systematic interval‑based sampling that reveals the dynamic evolution of charcoal properties as a function of residence time, rather than reporting only final product characteristics. These findings confirm that pyrolysis time is a key operational parameter and provide a practical basis for selecting optimal durations (120–180 min) to obtain structurally stable charcoal in small‑scale fixed‑bed reactors.